2016
DOI: 10.1186/s13059-016-1068-z
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic clock for gestational age at birth based on blood methylation data

Abstract: BackgroundGestational age is often used as a proxy for developmental maturity by clinicians and researchers alike. DNA methylation has previously been shown to be associated with age and has been used to accurately estimate chronological age in children and adults. In the current study, we examine whether DNA methylation in cord blood can be used to estimate gestational age at birth.ResultsWe find that gestational age can be accurately estimated from DNA methylation of neonatal cord blood and blood spot sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
303
8
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 232 publications
(331 citation statements)
references
References 62 publications
17
303
8
3
Order By: Relevance
“…DNAm GA was calculated as described elsewhere, 10 based on the methylation profile of 148 selected CpG sites. Chronological GA was based on ultrasound scans, and epigenetic GA was calculated as the arithmetic difference between DNAm GA and chronological GA and adjusted for chronological GA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNAm GA was calculated as described elsewhere, 10 based on the methylation profile of 148 selected CpG sites. Chronological GA was based on ultrasound scans, and epigenetic GA was calculated as the arithmetic difference between DNAm GA and chronological GA and adjusted for chronological GA.…”
Section: Methodsmentioning
confidence: 99%
“…9 These predictors are, however, not well suited for epigenetic age estimation at birth, because their correlation with chronological GA is nearly 0. 9 A recent study generated a novel epigenetic GA biomarker based on fetal umbilical cord blood or newborn blood spots, 10 which showed a high correlation with ultrasound-based GA. 10 This study demonstrated that lower epigenetic GA (lower DNAm GA than chronological GA) at birth was associated with maternal socioeconomic disadvantage and low birth weight. We have extended these analyses by showing that lower epigenetic GA was associated with maternal insulin-treated gestational diabetes mellitus in a previous pregnancy and in Sjögren syndrome, and higher epigenetic GA with a maternal age of more than 40 years at delivery, neonate’s lower 1-minute Apgar score, and female sex.…”
mentioning
confidence: 99%
“…Horvath's DNA methylation age was calculated using the agep function in the Cold Spring Harbor Laboratory Press on April 27, 2019 -Published by genome.cshlp.org Downloaded from wateRmelon R-package (Pidsley et al 2013). For newborns, we estimated the Knight's DNA methylation gestational age (Knight et al 2016). The pooled dataset was normalized using Funnorm (Fortin et al 2014).…”
Section: Biomarker Discovery: Creation Of a Lineage Invariant And Devmentioning
confidence: 99%
“…We used five independent datasets to evaluate the classification area under the ROC (AUROC) curve of the FCO signature and the stability of the FCO estimations (Supplemental Methods S1): UCB GSE80310 (Knight et al 2016), GSE74738 (Hanna et al 2016), GSE54399 (Montoya-Williams et al 2017, GSE79056 (Knight et Cold Spring Harbor Laboratory Press on April 27, 2019 -Published by genome.cshlp.org Downloaded from 20 al. 2016), GSE62924 (Rojas et al 2015).…”
Section: Auroc Stability Of the Fco Estimations And Synthetic Mixturmentioning
confidence: 99%
“…15 We have recently developed a method to predict gestational age at birth using DNAm at 148 CpG sites across the genome. 16 DNAm gestational age is highly correlated with clinically estimated gestational age. The residual between DNAm age and clinical gestational age, known as gestational age acceleration, has previously been associated with birth weight, which may reflect developmental maturity.…”
mentioning
confidence: 98%